Research on grounded theory influencing the dimensions of building resilient cities - Yuxi, Huang; Rehman, Asad Ur; ASSIM, ALIZA ABU H; Nawal, Ayesha; Talib, Zunirah Mohd (Edelweiss Applied Science and Technology, 2025)
In the current social landscape, the increasing frequency of urban disasters presents an undeniable challenge. Bolstering urban risk management mechanisms and establishing resilient city systems to safeguard the well-being of residents has emerged as a critical imperative within the field of urban management. This research adopted the grounded theory research paradigm, employing semi-structured interviews with 20 experts to explore the core influencing factors in the process of building resilient cities. Findings show that government regulation effectiveness, the capacity of companies to address risks, social organizations' involvement, and the overall level of urban risk management exert a significant impact on building resilient cities. Specifically, enhanced government regulation effectiveness can effectively promote the implementation of policies and institutional safeguards essential for resilient city construction. The improved risk response capabilities of companies provide more robust material and technical support when cities confront various types of disasters. Active social organizations' involvement facilitates the integration and utilization of community resources, strengthening the social resilience of cities in coping with disasters. Comprehensive enhancement of the city’s risk management capabilities is paramount, serving as the cornerstone for ensuring the overall effectiveness of efforts to build resilient cities, creating a safer and more sustainable urban environment.